Three-dimensional digitalized virtual planning for saphenous artery flap: a pilot study. Issue 1 (1st January 2016) - Zhang, Yuan Z.; Wen, Shu Z.; Zhang, Hui Q.; Li, Ya G.; Zhao, Jian M.; Yang, Yong
ABSTRACT: Objective: Since the 1970s, research and applications on flap and muscle flap had solved many problems in microsurgical reconstruction. However, the traditional flap design is completely dependent on two-dimensional (2D) images. The purpose of this study was to discuss the methods in the visualization of saphenous artery flap by digitalized technique and its applications by digitalized technique. Methods: Two adult fresh cadaver specimens, one male and one female, were subject to radiographic computerized tomography (CT) scanning before and after perfused with lead oxide–gelatine mixture, whose collimation are 0.625 mm (120 kV, 110 mA, 512 × 512 matrix). Through Amira 5.4.1 software, the 2D images in DICOM format were transformed into the 3D models of the entire region. The structures of saphenous artery were observed and the digitized visible models of saphenous artery flap were established through three-dimensional (3D) computerized reconstructions methods from these data using Amira 5.4.1 software. Next six cases of soft-tissue defects of the tibia region, involving the exposure bones underwent contrast-enhanced CT angiography of lower limbs utilizing a 64-row multi-slice spiral CT after median cubital vein injection with Ultravist (3.5 ml/s). 2D images from these data in DICOM format were transformed into computer. The structures of saphenous artery flap were observed and measured using Amira 5.4.1 software. Then, all cases were treated by saphenous artery flap. Results: The 3D reconstructed visible models established from these datasets perfectly displayed the saphenous artery flap anatomy. In six cases, the main trunk and branched of the blood vessels in the designed flap were consistent with the surgical findings. The starting point of the saphenous artery to the average distance of the knee clearance were 119.2 ± 9.6 mm, the average diameter of the saphenous artery from the starting point were 1.5 ± 0.3 mm. The range of flap was 8.0 × 5.0 cm to 20.0 × 8.0 cm. All flaps survived well. After 8–24 months' follow-up the knee flexion was 120–140°, the straight 0–10°. There was no case appeared incision infection. Conclusions: The preoperative use of 3D digitalized virtual planning for the saphenous artery flap improves the surgical accuracy, decreases the operation time and increases the survival rate of the flap.